2017
DOI: 10.1117/1.nph.4.2.025001
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine and IP3 receptor-mediated calcium signaling play a pivotal role in neurological infrared laser modulation

Abstract: Abstract. Pulsed infrared (IR) laser energy has been shown to modulate neurological activity through both stimulation and inhibition of action potentials. While the mechanism(s) behind this phenomenon is (are) not completely understood, certain hypotheses suggest that the rise in temperature from IR exposure could activate temperature-or pressure-sensitive ion channels or create pores in the cellular outer membrane, allowing an influx of typically plasma-membrane-impermeant ions. Studies using fluorescent inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 86 publications
(105 reference statements)
2
15
0
Order By: Relevance
“…These observations align with the response to infrared stimulation seen in neuroblastoma‐glioma and hippocampal neurons in vitro 40,41 . Pharmacology implicates IP 3 R as a primary pathway for the release of [Ca 2+ ] i from intracellular stores and is believed to be critical in numerous astrocytic functions 1,2 .…”
Section: Resultssupporting
confidence: 72%
“…These observations align with the response to infrared stimulation seen in neuroblastoma‐glioma and hippocampal neurons in vitro 40,41 . Pharmacology implicates IP 3 R as a primary pathway for the release of [Ca 2+ ] i from intracellular stores and is believed to be critical in numerous astrocytic functions 1,2 .…”
Section: Resultssupporting
confidence: 72%
“…Fractalkine has been shown to lead to increased cytosolic calcium in microglia [21]. Moreover, calcium antagonists are effective pain treatments [22]. In the present study, our results showed that [Ca 2+ ] i significantly increased after incubation with fractalkine in calcium-containing and calcium-free media, and this effect was dose-dependent.…”
Section: Discussionsupporting
confidence: 65%
“…Plasma membrane nanoporation has also been proposed 16 . Intracellular effects have also been demonstrated, particularly an increase of intracellular calcium ion concentration, originating from mitochondrial stores in cardiac cells 17 or from the endoplasmic reticulum, via activation of the phospholipase C and the inositol trisphosphate (IP 3 ) signaling pathway in neural and glial cells 18 , chinese hamster ovary cells, neuroblastoma-glioma cells 19 , and in cultured spiral ganglion neurons 20 . More recently, the role of the fast activation of voltage-dependent potassium ion channels in unmyelinated axons in the frame of infrared inhibition has been suggested in both modeling and experimental studies 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%